Child drowning prevention: GPS and LoRa based emergency alert system - Enam, Md. Rayef; Ghosh, Subhasish; Sarker, Dr. M. Mesbahuddin (AI Society & STMIK Indonesia, 2023)
UNICEF recently published in the